The UV-brightest Lyman continuum emitting star-forming galaxy. Issue 1 (30th July 2021) - Marques-Chaves, R; Schaerer, D; Álvarez-Márquez, J; Colina, L; Dessauges-Zavadsky, M; Pérez-Fournon, I; Saldana-Lopez, A; Verhamme, A
ABSTRACT: We report the discovery of J0121+0025, an extremely luminous and young star-forming galaxy ( M UV  = −24.11, log[$L_{\rm Ly \alpha } / \rm erg~s^{-1}] = 43.8$ ) at z  = 3.244 showing copious Lyman continuum (LyC) leakage ($f_{\rm esc, abs} \approx 40{{\ \rm per\ cent}}$ ). High signal-to-noise ratio rest-frame UV spectroscopy with the Gran Telescopio Canarias reveals a high significance (7.9σ) emission below the Lyman limit (<912 Å), with a flux density level f 900  = 0.78 ± 0.10μJy, and strong P-Cygni in wind lines of O vi  1033 Å, N v  1240 Å, and C iv  1550 Å that are indicative of a young age of the starburst (<10 Myr). The spectrum is rich in stellar photospheric features, for which a significant contribution of an AGN at these wavelengths is ruled out. Low-ionization interstellar medium (ISM) absorption lines are also detected, but are weak ($EW_{0} \rm \simeq 1$ Å) and show large residual intensities, suggesting a clumpy geometry of the gas with a non-unity covering fraction or a highly ionized ISM. The contribution of a foreground and AGN contamination to the LyC signal is unlikely. Deep optical to Spitzer/IRAC 4.5 μm imaging show that the spectral energy distribution of J0121+0025 is dominated by the emission of the young starburst, with log($M_{\star }^{\rm burst}/M_{\odot }) = 9.9\pm 0.1$ and $\rm SFR = 981\pm 232$  M⊙  yr −1 . J0121+0025 is the most powerful LyC emitter known among the star-forming galaxy population. The discovery of such luminous and young starburst leaking LyC radiation suggests that a significant fraction of LyC photons can escape in sources with a wide range of UV luminosities and are not restricted to the faintest ones as previously thought. These findings might shed further light on the role of luminous starbursts to the cosmic reionization.